2019
DOI: 10.26641/2307-0404.2019.3.181890
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of pregnancy in multidrug-resistant tuberculosis and type I diabetes mellitus comorbidities (a case report).

Abstract: 22. Lusiak M., Podwińska J. Interleukin 10 and its role in the regulation of the cell-mediated immune response in syphilis. Abstract. Clinical features of pregnancy in multidrug-resistant tuberculosis and type I diabetes mellitus comorbidities (a case report). Raznatovska O.M., Fedorec A.V., Shalmina M.O., Grekova T.A.Objective -to update the literature data with the clinical features of pregnancy in multidrug-resistant tuberculosis (MRD-TB) and type 1 diabetes mellitus (T1DM) comorbidities based on an example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In regard to TB outcomes, the majority of women in cases reported treatment completion, cure or improvement of clinical symptoms. 23–25 38 39 45 50–52 58 59 63–69 72–75 78 80 Other TB-related maternal outcomes included deaths, 19 21 28 30 32 33 36 41 42 47–49 56 81 82 lost to follow-up, 41 83 TB treatment failure 57 or unknown. 18 22 26 44 Across 16 case series, 19 29 49 53 61 76 77 81 83 a case-control study 41 and cohort studies 31 33 42 62 82 84 that provided descriptive data of TB outcomes, there were a total of 402 cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to TB outcomes, the majority of women in cases reported treatment completion, cure or improvement of clinical symptoms. 23–25 38 39 45 50–52 58 59 63–69 72–75 78 80 Other TB-related maternal outcomes included deaths, 19 21 28 30 32 33 36 41 42 47–49 56 81 82 lost to follow-up, 41 83 TB treatment failure 57 or unknown. 18 22 26 44 Across 16 case series, 19 29 49 53 61 76 77 81 83 a case-control study 41 and cohort studies 31 33 42 62 82 84 that provided descriptive data of TB outcomes, there were a total of 402 cases.…”
Section: Resultsmentioning
confidence: 99%
“… 33 Four studies reported successful treatment outcome (complete or cure) for the majority of their samples (83.3%, 61%, 65.4% and 88%) and lost to follow-up (11.1%, 28.6%, 26.9% and 12%). 42 62 82 84 The remaining studies, three case reports 57 72 78 and a case series, 19 provide conflicting results on maternal and fetal outcomes: two case studies reported good outcome for mother and baby, one case study reported treatment failure with induced abortion, while the case series noted maternal and fetal/newborn complications and deaths in their descriptive analysis. The validity and generalisability of these studies are limited by their study design and sample size.…”
Section: Resultsmentioning
confidence: 99%